2020
DOI: 10.1002/essoar.10503251.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Effects of Livestock Farming on Human Infections with Shiga Toxin-Producing Escherichia coli O157 in Small But Densely Populated Regions: The Case of the Netherlands

Abstract: The role of environmental transmission of typically foodborne pathogens like Shiga toxin-producing Escherichia coli (STEC) O157 is increasingly recognized. To gain more insights into spatially restricted risk factors that play a role in this transmission, we assessed the spatial association between sporadic STEC O157 human infections and the exposure to livestock (i.e. small ruminants, cattle, poultry, and pigs) in a densely populated country: the Netherlands. This was done for the years 2007-2016, using a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Living near cattle and other domesticated ruminants has been linked to STEC incidence, particularly for E. coli O157:H7. 2,[11][12][13][14][15] These studies suggest an important role for local reservoirs in STEC epidemiology. A comprehensive understanding of STEC's disease ecology would enable more effective investigations into potential local transmission systems and ultimately their control.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Living near cattle and other domesticated ruminants has been linked to STEC incidence, particularly for E. coli O157:H7. 2,[11][12][13][14][15] These studies suggest an important role for local reservoirs in STEC epidemiology. A comprehensive understanding of STEC's disease ecology would enable more effective investigations into potential local transmission systems and ultimately their control.…”
Section: Introductionmentioning
confidence: 78%
“…Our estimates are consistent with prior work that established an increased risk of STEC associated with living near cattle. 2,[11][12][13][14][15] We showed that 77% of strains infecting humans arose from cattle lineages. These transitions can be seen as a combination of the historic evolution of E. coli O157:H7 from cattle in the rare clades and the infection of humans from local cattle or cattle-related reservoirs in clade G(vi).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation